Economic values for traits in breeding objectives for sheep in the tropics: Impact of tangible and intangible benefits - Kosgey, I.S.; Arendonk, Johan A.M. van; Baker, R.L. (Elsevier, 2004)
In traditional management systems in the tropics, sheep constitute a source of easily convertible capital for financing purposes and insurance, a means of cultural and ceremonial functions, and a source of prestige, meat, manure and skins. In this study, breeding objectives were derived for an indigenous tropical sheep breed under pastoral production. Economic values were calculated for five situations: (i) base accounting for both tangible and intangible roles of sheep; (ii) accounting for manure, skins and intangible roles; (iii) accounting for 20% of animals sold, insurance, manure and skins; (iv) accounting for intangible roles only; and (v) accounting for tangible roles only. Sensitivity analysis to different levels of financing and insurance benefit factors, reproduction, survival and live weight traits was performed for the situation accounting for both tangible and intangible roles, and with a constant number of ewes. The economic value for a trait considered in a particular situation was calculated from the difference between the average performance level of the trait before and after incrementing it by one unit. The traits considered were litter size, lambing frequency, pre-weaning and post-weaning lamb survival to 12 months, ewe survival, 12-month lamb live weight, mature ewe live weight, consumable meat and kg manure dry matter sold ewe-1 year-1. Generally, in descending order of the profits and economic values, the situations studied ranked as follows: (i), (v), (iii), (ii) and (iv). For the base situation, financing and insurance benefits accounted for 13% and 6% of the total revenues, respectively. Situation (v) had a profit that was about 35% lower relative to situation (i). In terms of genetic standard deviations, the economic values (US$ ewe-1 year-1) for the base situation were: 2.81 for litter size, 6.40 for lambing frequency, 0.02 for pre-weaning survival, 0.03 for post-weaning survival, 0.05 for ewe survival, 1.81 for 12-month lamb live weight, 0.43 for mature ewe live weight, 0.09 for consumable meat and 0.01 for kg manure dry matter sold (ewe-1 year-1). The economic values indicate that litter size, lambing frequency and 12-month lamb live weight are likely to be important traits in pastoral production. Sensitivity analysis showed that future economic values for all the traits considered, except kg manure dry matter sold ewe-1 year-1, might change depending on levels of intangible benefit factors. Ewe survival and mature ewe live weight were not responsive to changes in reproductive traits, and pre- and post-weaning traits, and vice versa. It is concluded that it is necessary to include the intangible roles of sheep in tropical breeding programmes.